(untitled) (Research, Society and Development, 2022)
The present work aims to investigate the health conditions of professors from a federal institution of higher education in the interior of northeastern of Brazil. This is a descriptive cross-sectional study, carried out with 39 professors from the Federal University of Sergipe. Of the 39 interviewees, the majority were female, married, white and with a doctorate. It was found that 74% (n=29) of the professionals declared dissatisfied / very dissatisfied with the activities developed at work and 31% (n=12) reported some morbidity. Among the referred morbidities, there was a higher prevalence of diseases related to mental health (50%; n=6). The data obtained show a high prevalence of dissatisfaction with the activities developed in teaching, as well as worsening mental health, despite the relatively high motivation and quality of life at work.